From slavery to 9/11 readings in the sociology and social psychology of extreme situations - Langer, Sidney (Pearson, 2012)
An edited collection of readings exploring sociological and social psychological analysis of extreme situations From Slavery to 9/11: Readings in the Sociology and Social Psychology of Extreme Situations explores the social structure of total institutions and extreme situations and survival and coping mechanisms used by the people who have been affected by these institutions and events. Topics include many of the defining events of the 19th and 20th centuries and the beginning of the 21st century: institutionalized slavery; genocidal atrocities and the Holocaust; September 11, 2001; and Hurricane Katrina. Learning Goals Upon completing this book, readers will be able to: * Explore historical and contemporary events * Make connections between the institutions and events explored in the book * Understand how people in total institutions, survivors of man-made disasters, and victims of natural disasters cope with their experiences.